Robust and Stable Ratiometric Temperature Sensor Based on Zn–In–S Quantum Dots with Intrinsic Dual‐Dopant Ion Emissions. (13th September 2016) - Cao, Sheng; Zheng, Jinju; Zhao, Jialong; Yang, Zuobao; Shang, Minghui; Li, Chengming; Yang, Weiyou; Fang, Xiaosheng
Abstract : Dual emission quantum dots (QDs) have attracted considerable interest as a novel phosphor for constructing ratiometric optical thermometry because of its self‐referencing capability. In this work, the exploration of codoped Zn–In–S QDs with dual emissions at ≈512 and ≈612 nm from intrinsic Cu and Mn dopants for ratiometric temperature sensing is reported. It is found that the dopant emissions can be tailored by adjusting the Mn‐to‐Cu concentration ratios, enabling the dual emissions in a tunable manner. The energy difference between the conduction band of the host and Cu dopant states is considered as the key for the occurrence of Mn ion emission. The as‐constructed QD ratiometric temperature sensor exhibits a totally robust stability with a fluctuation of ≈ I Cu / I tot versus times lower than 1% and almost no hysteresis in cycles over a broad window of 100–320 K. This discovery represents that the present cadmium‐free, intrinsic dual‐emitting codoped QDs can open a new door for the synthesis of novel QDs with stable dual emissions, which poise them well for challenging applications in optical nanothermometry. Abstract : A robust and stable ratiometric temperature sensor based on Zn–In–S QDs with intrinsic dual‐dopant ion emissions is investigated. The fluctuation of ≈ I Cu / I tot versus time is lower than 1% and the sensor shows almost no hysteresis in cycles over a broad operating temperature window from 100 to 320 K.